The influence of working experiences in generating leadership skills in Malaysia France Institute - 185478 Azman Ahmad; Muhd. Rashid Rajuddin; Fakulti Pendidikan (1999)
Thesis (Sarjana Pendidikan (Teknik dan Vokasional)) - Universiti Teknologi Malaysia, 1999